The Utilization of Historical Heritage in Bengkulu City as a Source of Social Studies Learning: Study at SMP Negeri 13 Kota Bengkulu - Rossi Delta Fitrianah; Abdul Malik Chaniago (Indonesian Journal of Social Science Education (IJSSE), 2025)
Bengkulu has many historical heritages that have the potential to be used as social studies learning resources in secondary schools. This research aims to: 1) describe the historical heritage used by social studies teachers at SMP Negeri 13 Bengkulu City as a social studies learning resource; 2) analyze the social studies teacher's strategy in utilizing historical heritage as a learning resource. This research was conducted using a qualitative descriptive method. The research was conducted at SMP Negeri 13 Bengkulu City. Data collection was carried out using several techniques, namely in-depth interviews with teachers and students, teacher teaching observations and document analysis in the form of lesson plans and syllabi. Based on the research carried out, the results were obtained that: 1) there are three historical heritages in Bengkulu City which are used as social studies learning resources, namely Fort Marlborough, Bung Karno's residence and Fatmawati's house. These three historical relics were chosen by teachers as social studies learning resources because they are relevant to the learning topic and close to the students' environment; 2) in utilizing historical heritage as a social studies learning resource, teachers use field trip learning methods as the main strategy. This method is used because it is considered to arouse students' enthusiasm and attraction. Apart from that, teachers also utilize existing historical heritage through pictures, videos and visual aids/miniatures.